2006
DOI: 10.1073/pnas.0508295103
|View full text |Cite
|
Sign up to set email alerts
|

BLAP75/RMI1 promotes the BLM-dependent dissolution of homologous recombination intermediates

Abstract: BLM encodes a member of the highly conserved RecQ DNA helicase family, which is essential for the maintenance of genome stability. Homozygous inactivation of BLM gives rise to the cancer predisposition disorder Bloom's syndrome. A common feature of many RecQ helicase mutants is a hyperrecombination phenotype. In Bloom's syndrome, this phenotype manifests as an elevated frequency of sister chromatid exchanges and interhomologue recombination. We have shown previously that BLM, together with its evolutionarily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
261
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(270 citation statements)
references
References 35 publications
9
261
0
Order By: Relevance
“…However, the ability of type IA topoisomerases to pass one ssDNA through the other makes these enzymes an ideal agent in removing the topological linkages in between dHJ (5). Recent work has shown that several type IA topoisomerases, in association with BLM, are capable of removing the last two linkages from an oligonucleotide-based substrate (24,31). In this work, we have shown that DmTopo III␣, in association with DmBlm, is capable of catalyzing the earlier steps of convergent branch migration of the HJs.…”
Section: Discussionmentioning
confidence: 58%
“…However, the ability of type IA topoisomerases to pass one ssDNA through the other makes these enzymes an ideal agent in removing the topological linkages in between dHJ (5). Recent work has shown that several type IA topoisomerases, in association with BLM, are capable of removing the last two linkages from an oligonucleotide-based substrate (24,31). In this work, we have shown that DmTopo III␣, in association with DmBlm, is capable of catalyzing the earlier steps of convergent branch migration of the HJs.…”
Section: Discussionmentioning
confidence: 58%
“…Mechanistically, the human BLM helicase works together with topoisomerase IIIa and the BLAP75/Rmi1 protein to branch migrate and decatenate dHJs into noncrossovers (Wu and Hickson 2003;Raynard et al 2006;Wu et al 2006). It is expected that Sgs1, the likely BLM ortholog in Saccharomyces cerevisiae, also functions in this manner to resolve dHJs into noncrossover during DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by the cancer-predisposition disorder, Bloom's syndrome, which is caused by mutation in the human BLM gene (reviewed in German, 1993). Because the BLM protein, in conjunction with its associated proteins, hTOPOIII␣ and hRMI1 (Johnson et al, 2000;Wu et al, 2000;Yin et al, 2005), can catalyze dissolution of HRR intermediates in vitro Plank et al, 2006;Raynard et al, 2006;Wu et al, 2006), it is likely that unprocessed and/or aberrantly processed HRR intermediates at least partly contribute to the cellular defects in Bloom's syndrome. Indeed, Bloom's syndrome cells classically demonstrate elevated levels of sister chromatid exchanges, mitotic recombination, and genome instability.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that we do not know presently if the X-molecules arising in MMS-treated sgs1, rmi1, and TOP3 Y356F strains are identical or if they represent different types of HRR intermediates that cannot readily be distinguished by the 2D gel technique. One possibility, based on the known enzymatic functions of BLM, hTOPOIII and RMI1 Plank et al, 2006;Raynard et al, 2006;Wu et al, 2006), is that X-molecules arising in sgs1 mutants are double Holliday junctions, whereas those arising in TOP3 Y356F , or rmi1, mutants are hemicatenanes formed by the Sgs1-dependent convergent branch migration of double Holliday junctions. Surprisingly, we found that although mutation of RAD51 prevented persistent MMS-induced HRR intermediates in sgs1, rmi1, and TOP3 Y356F cells, mutation of SHU1 did not.…”
mentioning
confidence: 99%